PENGARUH PENGALAMAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. SUMBER JADI KENCANA MOTOR - Imam Ikhwana; Yusriadi Yusriadi (Jurnal Daya Saing, 2026)
This study aims to determine and analyze the effect of work experience and work discipline on employee performance at PT. Sumber Jadi Kencana Motor. This research employed a quantitative method with a saturated sampling technique involving 58 employees. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 26. The results indicate that work experience has a positive and significant effect on employee performance (t-value = 7.791 > t-table = 2.004; significance = 0.000 < 0.05), while work discipline does not have a significant partial effect on employee performance (t-value = 1.652 < t-table = 2.004; significance = 0.104 > 0.05). Simultaneously, work experience and work discipline have a significant effect on employee performance (F-value = 30.350 > F-table = 3.16; significance = 0.000 < 0.05). Keywords: Work Experience, Work Discipline, Employee Performance